The therapeutic influence of epsilon3 isoform of apolipoprotein E on pathophysiological mechanisms of secondary brain injury evolution after experimental traumatic brain injury - Vadym Biloshytsky (Ukrainian Neurosurgical Journal, 2012)
Purpose. To test the therapeutic potential of apolipoprotein E isoform epsilon3, whose synthesis in nerve tissue was induced by means of gene therapy, in an experimental traumatic brain injury (TBI) model, and to substantiate its mechanism of therapeutic action based on current literature data.Methods. To determine structural and functional changes associated with severe diffuse TBI, adult male Wistar rats were subjected to weight drop impact acceleration injury and evaluated at day 10 after trauma. A mixture of DOTAP liposomes and 25 µg of recombinant plasmid pCMV-APOE3 cDNA was infused intraventicularly immediately after TBI using ALZET osmotic pumps. The hippocampal CA1 regions were analyzed by means of light and electron microscopy, morphometry, immunocytochemical and confocal analysis using markers selective for neurons (NeuN) and astrocytes (GFAP). The neurofunctional outcome was assessed in an open field test.Results. The research data have shown that cationic liposome-mediated APOE3 gene transfer has a beneficial effect on hippocampal structure and ultrastructure, diminishes neuronal loss and severity of diffuse axonal injury, gliosis and microglial reaction, as well as aids regression of posttraumatic stress and anxiety.Conclusion. According to literature data, possible mechanisms of apoE therapeutic action are (1) normalization of neural cellular lipid component, (2) its role in regulating reactive gliosis and inflammatory response of CNS to injury, (3) antioxidant effects of apolipoprotein E, (4) regulation of cell death mechanisms, (5) influence of apolipoprotein E on differential gene expression and regulation of genomic response of CNS cells to injury